The future of thermal comfort in an energy- constrained world - Law, Tim (Springer Theses, Recognizing Outstanding Ph.D. Research, 2013)
The dissertation investigates the scientific and business factors that have resulted in air-conditioning being a major contributor to climate-change. With his architectural background, the author demonstrates how a design methodology, not commonly adopted in scientific studies, may actually be a suitable way of dealing with a complex problem: the 'business as usual' scenario involving building science, sociological values and consumer behavior. Using his innovations as case studies, the author shows how good ideas cannot be evaluated on scientific merit alone and demonstrates why commercialization may have a pivotal role in deployment of research-based technology. He advances the theory of personalized thermal comfort which can potentially resolve the air-conditioning conundrum.